Scholarship from National Scholarship Institute for a Ph.D. research - Skarlatos, Dimitrios (My University, 2026)
Scholarship from National Scholarship Institute for a Ph.D. research in Digital Photogrammetry (after written exams). Duration 3.5 years
Keywords: Sciences